Assessing the Impacts of Broken Windows Policing Strategies on Citizen Attitudes in Three California Cities: Redlands, Ontario and Colton, 2008-2009 - Weisburd, David ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study examined the impact that a six-month broken windows style policing crackdown on disorder had on residents of three California cities: Colton, Ontario and Redlands. The study investigated four questions: What is the impact of broken windows policing on fear of crime among residents of the targeted hot spots? What is the impact of broken windows policing on police legitimacy in the targeted hot spots? What is the impact of broken windows policing on reports of collective efficacy in the targeted hot spots? Is broken windows policing at hot spots effective in reducing both actual and perceived levels of disorder and crime in the targeted hot spots? To answer these questions, a block randomized experimental design was employed to deliver a police intervention targeting disorder to 55 treatment street segments with an equal number of segments serving as controls. Data were collected on the type and amount of crime before, during, and after implementation as well as interviews of residents before and after the crackdown in order to gauge their perception of its success.